《南洋商报》对新马“华语电影”的讨论（1950-1965）= A study of Singapore-Malaya “Chinese-language cinema” in Nanyang Siang Pau（1950-1965) - 杨珺涵 Yeo, Jun Han (2012)
新加坡及马来亚电影起源于20世纪20年代。五十年代本土华裔导演易水早就指出，最初从事本地电影制作的是华语电影工作者，接下来才有马来影片的摄制。这显示“华语电影”在本土早已登陆且成型。“华语电影”此词包含了重大的意义，因为它的兴起成为了日后全球华语电影界通用的专属名词。近几年，“华语电影”此词的兴起成为了学界讨论的课题之一，而学者们推论出“华语电影”的起源是在本土50年代。但是，目前对于这时期本土“华语电影”的资料记录甚少，而且大部分华语电影的拷贝已散失。虽然仅存的资料非常有限，但本文将借由当时盛行的《南洋商报》来为新马电影史建构一个更完整的面貌。本文将整理以及归纳《南洋商报》1950至1965年新马“华语电影”的19部重要代表作及讨论，来重拾这遗失在电影史中的沧海遗珠。The rise of Singapore and Malaya films was in the 1950s. The local ethnic Chinese director Yi Sui pointed out that the pioneer in the local film production was the Chinese film crew, followed by the Malay film crew. This shows that Chinese-Language film has gained a foothold in Singapore and Malaya long before its time. The term “Chinese-Language film” holds a great significance as its emergence revolves into a global exclusive term for all Chinese movies. In recent years, the emergence of the term “Chinese-Language film” has become one of the topics in the academic discussion. Scholars deduced that the emergence of the term “Chinese-language film” is in the 1950s Malaya-Singapore. However, there are few data records for this period and most of the duplicates for the Chinese-Language films have been lost. Nevertheless, I will be collating the studies of the “Chinese Language Films” through the prevalent "Nanyang Siang Pau” to reconstruct the outlook of the Singapore-Malaya Chinese-Language films from 1950 to 1965. In particular, I will be focusing on 19 important Chinese-Language films as my objects of study, in hope of restoring this long lost period in the film history.